P16INK4A, CDC6, and MCM5: predictive biomarkers in cervical preinvasive neoplasia and cervical cancer. Issue 5 (27th April 2005) - Murphy, N; Ring, M; Heffron, C C B B; King, B; Killalea, A G; Hughes, C; Martin, C M; McGuinness, E; Sheils, O; O'Leary, J J
Abstract : Aim: To analyse and compare expression patterns of three potential biomarkers—p16 INK4A, CDC6, and MCM5—and evaluate their use as predictive biomarkers in squamous and glandular cervical preinvasive neoplasia. Methods: Immunocytochemical analysis of p16 INK4A, MCM5, and CDC6 expression was performed on 20 normal, 38 cervical intraepithelial neoplasia 1 (CIN1), 33 CIN2, 46 CIN3, 10 squamous cell carcinoma, 19 cervical glandular intraepithelial neoplasia (cGIN), and 10 adenocarcinoma samples. Staining intensity was assessed using a 0–3 scoring system. p16 INK4A, MCM5, and CDC6 expression was also examined in ThinPrep slides exhibiting mild, moderate, and severe dyskaryosis. Human papillomavirus (HPV) was detected using a modified SYBR green assay. Fluorogenic polymerase chain reaction (PCR) and solution phase PCR were used for specific HPV typing. Results: All three markers showed a linear correlation between expression and grade of dysplasia. p16 INK4A and MCM5 protein expression was upregulated in all grades of squamous and glandular dysplasia. CDC6 protein was preferentially expressed in high grade lesions and in invasive squamous cell carcinoma. Conclusion: p16 INK4A expression was closely associated with high risk HPV infection—all grades of squamous and glandular cervical lesions were immunohistochemically positive. MCM5 staining intensity was independent of high risk HPV infection, highlighting its potential as a biomarker in both HPV dependent and independent cervical dysplasia. CDC6 may be a biomarker of high grade and invasive lesions of the cervix, with limited use in low grade dysplasia. p16 INK4A was the most reliable marker of cervical dysplasia. Combinations of dysplastic biomarkers may be useful in difficult diagnostic cases.